Local Islam and the Pegon Literacy Tradition: An Examination of al-Iṭmi’nan as a Vernacular Representation of Qami’ al-Tughyan by K.H. Zaenal Arifin of Tegal (1935-1991) - Akhmad Yunizar; Jamaluddin, Jamaluddin (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2025)
This study explores the life and theological contributions of K.H. Zaenal Arifin (1935–1991), an Islamic scholar from Demangharjo, Tegal. He is known for authoring Al-Itmi’nan, a Javanese Pegon-script translation of Qami‘ al-Tughyan ‘ala Manzumati Shu‘ab al-Iman, which covers 77 branches of faith. The research employs historical methods, including data collection, source criticism, interpretation, and historiography, drawing on both literature and interviews. It employs biographical theory to trace Arifin’s life and vernacularization theory to analyze his use of the Pegon script. Born in Suradadi in 1935, Arifin studied at several pesantren, including Tebuireng and Krapyak, and completed his formal education at Sunan Kalijaga State Islamic University in Yogyakarta. Influenced by K.H. Bisri Mustofa, he wrote Al-Itmi’nan, later published by Menara Kudus. The book is rich in textual references and includes a poetic version of Asma al-Husna by K.H. Ali Maksum. Its creation was driven by Arifin’s devotion to God, filial duty, and the community’s requests. Ultimately, Al-Itmi’nan embodies both Arifin’s intellectual heritage and his contribution to the vernacularization of Islamic knowledge through the medium of Pegon literacy, particularly in the field of theology (tawhid), which constitutes the foundational core of Islamic teachings